2022
DOI: 10.3390/diagnostics12081961
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings in Patients with Immune Checkpoint Inhibitor-Induced Arthritis

Abstract: Immune checkpoint inhibitor (ICI)-induced arthritis is an increasingly recognized adverse event in patients with oncologic disease during immunotherapy. Four patterns are well described, including rheumatoid arthritis (RA)-like, polymyalgia rheumatica (PMR)-like, psoriatic arthritis (PsA)-like, and oligo-monoarthritis, among others. Despite better clinical recognition of these syndromes, information about the main imaging findings is limited. Methods: We conducted a retrospective observational study including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…One third exhibited peripheral 18 F-FDG uptake. These results were confirmed recently by Ponce et al ( 44 ). To note, patients experienced irAEs induced by ICI had a better cancer prognosis than those in non – irAEs patients ( 46 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…One third exhibited peripheral 18 F-FDG uptake. These results were confirmed recently by Ponce et al ( 44 ). To note, patients experienced irAEs induced by ICI had a better cancer prognosis than those in non – irAEs patients ( 46 ).…”
Section: Introductionsupporting
confidence: 88%
“…Compared with classical PMR, PMR-like syndromes showed higher prevalence of peripheral arthritis and the biologic inflammation can be lacking ( 43 ). Previous report ( 44 ) and van der Geest et al ( 45 ) assessed the role of 18 F-FDG PET-CT before the initiation of corticosteroid in 6 patients with PMR – like syndrome. He found the same symmetric 18 F-FDG uptake locations than those in classical PMR, without LVV associated.…”
Section: Introductionmentioning
confidence: 99%
“…FDG PET patterns mimic rheumatoid arthritis (RA), polymyalgia rheumatica (PMR), psoriatic arthritis (PsA), and oligo-monoarthritis [105]. Ponce et al (2022) categorized ICI-arthritis into self-limiting (>50%), intermittent (25%), or persistent chronic types (20%) [74,93,104,106]. A review by Cappelli et al (2017) indicated that the incidence of the two most common irAEs, arthralgia and myalgia, was found in 1-43% and 1-21% of patients, respectively [54,107].…”
Section: Musculo-skeletalmentioning
confidence: 99%
“…Arthritis has typically been controlled by ultrasound, MRI, or CT; however, FDG PET use has been growing in the field of arthritis, and it is even more sensitive in cases of soft tissue irAEs, such as synovitis, myositis, and fasciitis, where it shows diffuse periarticular uptake [ 104 ]. FDG PET patterns mimic rheumatoid arthritis (RA), polymyalgia rheumatica (PMR), psoriatic arthritis (PsA), and oligo-monoarthritis [ 105 ].…”
Section: Iraes Caused By Immune Checkpoint Inhibitors and Their Manif...mentioning
confidence: 99%
“…In recent years, reports of inflammatory arthritis after ICI administration have been increasing [ 81 , 82 , 83 , 84 , 85 , 86 ]. Arthritis is more common with PD-1/PD-L1 blockade than with CTLA-4 blockade [ 39 ], but the combination carries the highest risk [ 87 ].…”
Section: Rheumatic Iraesmentioning
confidence: 99%